A high-capacity sodium-ion battery negative electrode material and a preparation method thereof
By creating pores on a carbon material substrate and in situ synthesizing transition metal sulfides, the sodium storage capacity and volume expansion problems of sodium-ion battery negative electrode materials were solved, achieving high capacity and stable electrochemical performance.
Patent Information
- Application Number
- CN202311483152.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-08
- Publication Date
- 2025-10-17
- Estimated Expiration
- 2043-11-08
AI Technical Summary
When existing carbon materials are used as negative electrode materials for sodium-ion batteries, they have problems such as limited sodium storage capacity, volume expansion, and pulverization during the insertion/extraction of sodium ions, resulting in reduced electrochemical activity.
Pores are created on a carbon material substrate and transition metal sulfides are synthesized in situ, which inhibits volume expansion through the confinement of the pores and improves the ion transport path and electron transport efficiency.
It improves the specific capacity and cycle stability of sodium-ion batteries, inhibits the expansion of transition metal sulfides, and enhances the electrochemical properties of the material.
Smart Images

Figure CN117638021B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of sodium ion batteries, and particularly relates to a high-capacity sodium ion battery negative electrode material and a preparation method thereof. BACKGROUND
[0002] With the increasing demand for energy due to technological development and the demand for renewable energy due to environmental protection, the development of energy storage technology has become crucial. Lithium ion batteries, as a mature energy storage technology, are widely used, but their cost problems and uneven resource distribution have gradually become prominent. Sodium ion batteries, as a potential alternative technology, have received increasing attention. Due to the abundance of sodium in the earth's crust, sodium ion batteries have lower costs and more extensive resource distribution compared to lithium ion batteries.
[0003] Carbon materials are the most widely studied negative electrode materials for sodium ion batteries. Similar to lithium ion batteries, carbon materials have excellent electrical conductivity and structural stability, making them one of the ideal negative electrode materials. Common sodium ion negative electrode materials include hard carbon and soft carbon. However, the theoretical sodium storage capacity of carbon materials is limited. Therefore, finding new negative electrode materials to improve the performance of sodium ion batteries is a current research hotspot.
[0004] Transition metal sulfides as negative electrode materials for sodium ion batteries have attracted widespread attention and research. This type of material has rich structural diversity and excellent electrochemical performance, making it a promising choice for improving the performance of sodium ion batteries. Transition metal sulfides can provide higher capacity than carbon materials, however, during the sodium ion insertion / extraction process, transition metal sulfides will experience volume expansion, pulverization, and other problems, resulting in loss of electrochemical activity and limiting their practical application. SUMMARY
[0005] In view of the defects in the prior art, the present application aims to provide a high-capacity sodium ion battery negative electrode material and a preparation method thereof. The method synthesizes transition metal sulfides in situ inside the pores after creating pores on the carbon material substrate, and the constraint effect of the pores inhibits the expansion of transition metal sulfides.
[0006] In the present application, the high-capacity sodium ion battery negative electrode material has transition metal catalytic etching to create pores, increasing the ion transport path and improving the rate performance of the carbon material substrate; the transition metal sulfides embedded inside the etching pores are constrained by the pore walls, inhibiting the volume expansion generated during the cycling process. In addition, the carbon material substrate has good electrical conductivity, further improving the electron transport efficiency during the reaction process of the transition metal particles.
[0007] In a first aspect, the present invention provides a high-capacity sodium ion battery negative electrode material, wherein the high-capacity sodium ion battery negative electrode material comprises a carbon material substrate and a transition metal sulfide grown in situ and embedded in the carbon material substrate.
[0008] Preferably, the transition metal in the transition metal sulfide is at least one of Mo, Co, Fe, Ni, and Mn.
[0009] Preferably, the carbon material substrate is hard carbon, soft carbon, graphite, expanded graphite, mesophase carbon microbeads or carbon fibers.
[0010] In a second aspect, the present invention further provides a method for preparing a high-capacity sodium ion battery negative electrode material, comprising:
[0011] (1) mixing a carbon material substrate with a transition metal salt solution, stirring and drying to obtain a carbon material substrate with a surface loaded with a transition metal salt, and subjecting the mixture to high temperature treatment under an inert atmosphere to obtain a carbon material substrate with a surface loaded with transition metal particles;
[0012] (2) introducing an etchant into the obtained carbon material substrate loaded with transition metal particles under an inert atmosphere and etching it under heating conditions to form a porous structure in the carbon material substrate and embed the transition metal particles into the porous structure to form a porous carbon material substrate embedded with transition metal particles;
[0013] (3) Premixing a porous carbon material substrate embedded with transition metal particles with sulfur powder, and performing high-temperature sulfurization under an inert atmosphere to in situ synthesize transition metal sulfides within the porous structure.
[0014] Preferably, in step (1), the solvent of the transition metal salt solution is at least one of water, ethanol, and acetone; the transition metal salt is an organic salt or an inorganic salt of a transition metal; the organic salt is at least one of formate, acetate, ethanol, citrate, and acetylacetonate; the inorganic salt is at least one of hydrochloride, sulfate, nitrate, phosphate, hypophosphite, chlorate, perchlorate, and aminosulfonate; and the molar concentration of the transition metal salt solution is 0.01 to 2 mol / L.
[0015] Preferably, in step (1), the stirring and drying temperature is 60 to 90° C., and the time is 1 to 20 hours;
[0016] The inert atmosphere is at least one of argon, nitrogen, helium, and carbon monoxide; the flow rate of the inert atmosphere is 50 to 1000 mL / min;
[0017] The temperature of the high temperature treatment is 400-1000°C, the time is 1-10 hours, and the heating rate is 1-20°C / min; preferably, the temperature of the high temperature treatment is 500-700°C, the time is 1-4 hours, and the heating rate is 5-10°C / min.
[0018] Preferably, in step (1), the particle size of the transition metal particles is 5 nm to 2 μm.
[0019] Preferably, in step (2), the high-temperature etching specifically includes: heating the carbon material substrate with transition metal particles loaded on the surface to the etching temperature under an inert atmosphere, introducing an etchant, and under the catalytic action of the transition metal particles, the etchant etches along the loading sites of the transition metal particles, and the transition metal particles enter the interior along the pores during the etching process.
[0020] Preferably, in step (2), the flow rate of the inert atmosphere is 50 to 1000 mL / min;
[0021] The high temperature etching temperature is 700-1000°C, the time is 0.5-10h, and the heating rate is 1-20°C / min;
[0022] The etchant is an alkaline etchant or a gas etchant; the alkaline etchant is sodium hydroxide, lithium hydroxide or potassium hydroxide; the gas etchant is water vapor or oxygen; the alkaline etchant is introduced by pre-grinding the alkaline etchant and the carbon material substrate loaded with transition metal particles uniformly before heating; the molar ratio of the alkaline etchant to the carbon material substrate loaded with transition metal particles is 1:10 to 10:1;
[0023] The gas etchant is introduced in the following manner: at an etching temperature, the gas etchant is introduced at a flow rate of 0.05 to 1 mL / min;
[0024] When the etchant is an alkali etchant, the method for removing the alkali etchant is: using deionized water to dissolve and wash away the alkali and its reaction by-products.
[0025] Preferably, in step (3), the molar ratio of the sulfur powder to the carbon material substrate is (1-8):1, preferably (2-4):1.
[0026] Preferably, in step (3), the high temperature vulcanization is a step-by-step temperature increase procedure, comprising: heating to 95°C to 300°C at a heating rate of 1 to 10°C / min and keeping the temperature for 1 to 10 hours, and then continuing to heat to 450°C to 700°C and keeping the temperature for 1 to 12 hours.
[0027] Preferably, the preparation method further comprises: performing carbon coating on the surface of the high-capacity sodium ion negative electrode material; the carbon coating comprises: taking sucrose or pitch as a carbon source, dissolving in a solvent, mixing with the high-capacity sodium ion negative electrode material and drying, pyrolyzing under an inert atmosphere to form a carbon coating structure on the surface of the high-capacity sodium ion negative electrode material; wherein the mass ratio of the carbon source to the high-capacity sodium ion negative electrode material is 3:20-1:1; the solvent is at least one of deionized water, ethanol, tetrahydrofuran and isopropanol; the temperature of the stirring and drying is 40-120 DEG C, and the time is 0.5-12 hours; the temperature of the pyrolysis is 400 DEG C-1000 DEG C, the time is 1-12 hours, and the temperature rising rate is 1-10 DEG C / min.
[0028] The high-capacity sodium ion battery negative electrode material provided by the application is a material in which transition metal sulfide is synthesized in situ on a carbon material substrate, the carbon material substrate has etching holes obtained by catalytic etching of corresponding transition metals, transition metal particles enter the etching holes, and transition metal sulfide is obtained by in-situ sulfuration, and the transition metal sulfide is embedded in the etching holes of the carbon material substrate due to the constraint of the hole walls.
[0029] In the preparation method of the high-capacity sodium ion battery negative electrode material, transition metal salt is compounded with a carbon material substrate, and the transition metal salt is pyrolyzed under an inert atmosphere to generate transition metal particles on the surface of the carbon material substrate. Subsequently, the carbon material substrate with the transition metal particles loaded on the surface is etched at high temperature, and due to the catalytic effect of the transition metal particles on the activation of the carbon material substrate, the etchant continuously reacts with carbon atoms in the carbon material at the position where the transition metal particles are loaded, and the carbon material substrate is etched to generate a hole structure. The transition metal particles not only act as a catalyst to catalyze the etching process and enter the etching holes during the etching process to generate transition metal sulfide in situ and embed the structure in the carbon material substrate. Surface carbon coating can further optimize the structure and inhibit the polysulfide shuttle effect in the reaction process. The specific capacity of the high-capacity sodium ion battery negative electrode material prepared by the application can reach 700 mAh g -1 , and the first coulombic efficiency is 70%-98.1%.
[0030] The carbon material etching hole provided by the application is beneficial to providing a channel for sodium ions to enter the inside of the carbon material, and improves the rate performance of the carbon material substrate; the generated transition metal sulfide is secondarily used for the catalyst nickel, the generated transition metal sulfide has extremely high theoretical sodium storage capacity, and the sodium storage capacity of the composite carbon material is increased; in the cycle process, the transition metal sulfide will be expanded and pulverized due to the deintercalation of sodium ions, loses sodium storage activity, and polysulfides will be generated in the reaction and dissolved into the electrolyte, and the cycle performance is reduced due to the shuttle effect of polysulfides, while the in-situ synthesized transition metal sulfide in the pore channel is constrained by the pore wall and the expansion in the cycle is inhibited, and the diffusion of polysulfides in the electrolyte is limited by the pore channel, and the shuttle effect of polysulfides is slowed down, so that the cycle stability is improved.
[0031] Advantages:
[0032] (1) In the application, the transition metal simultaneously plays a dual role of etching catalyst and transition metal sulfide precursor in the carbon material substrate, and the transition metal particles are ingeniously introduced into the inside of the carbon material substrate, and the transition metal sulfide is in-situ synthesized, the process is simple, and the raw materials are easy to obtain.
[0033] (2) The in-situ synthesized transition metal sulfide is constrained by the pore wall structure inside the pore, forms a structure in which the transition metal sulfide is embedded in the inside of the pore, inhibits the volume expansion of the transition metal sulfide in the sodium ion deintercalation process through the constraint of the pore wall, increases the cycle stability, and performs carbon coating on the surface to inhibit the shuttle effect of polysulfides in the reaction process.
[0034] (3) By adjusting the type of transition metal salt, etching time, etching temperature, and sulfur ratio, the size and depth of the pores of the carbon material substrate and the type of transition metal sulfide can be controlled, different types of transition metal sulfides can be matched for different types of carbon material substrates, different coating processes can be selected for different types of carbon material substrates, the process is flexible and easy to control, and industrial scale production can be realized. BRIEF DESCRIPTION OF DRAWINGS
[0035] Figure 1 A scanning electron microscope image of nickel particles decomposed from nickel acetate loaded on the surface of hard carbon in Example 1;
[0036] Figure 2 A scanning electron microscope image of nickel particles etched into the inside of hard carbon after water vapor etching in Example 1;
[0037] Figure 3 A scanning electron microscope image of nickel disulfide composite hard carbon material obtained after in-situ sulfidation in Example 1;
[0038] Figure 4 A charge-discharge curve of the nickel disulfide composite hard carbon material in Example 1;
[0039] Figure 5 Scanning electron microscope image of nickel particles supported on hard carbon surface after decomposition of acetylacetone nickel in Example 2;
[0040] Figure 6 Scanning electron microscope image of nickel particles etched into hard carbon in Example 2 after water vapor etching;
[0041] Figure 7 Scanning electron microscope image of nickel disulfide composite hard carbon material obtained after in-situ sulfurization in Example 2;
[0042] Figure 8 Charge-discharge curve of nickel disulfide composite hard carbon material in Example 3;
[0043] Figure 9 Scanning electron microscope image of carbon-coated nickel disulfide composite hard carbon material in Example 3;
[0044] Figure 10 Charge-discharge curve of carbon-coated nickel disulfide composite hard carbon material in Example 3;
[0045] Figure 11 Scanning electron microscope image of nickel disulfide composite expanded graphite material obtained after in-situ sulfurization in Example 4;
[0046] Figure 12 X-ray diffraction pattern of nickel disulfide composite expanded graphite material in Example 4;
[0047] Figure 13 Charge-discharge curve of nickel disulfide composite expanded graphite material in Example 4;
[0048] Figure 14 Cyclic voltammogram of nickel disulfide composite expanded graphite material in Example 4;
[0049] Figure 15 Charge-discharge curve of nickel disulfide composite hard carbon material in Example 5;
[0050] Figure 16 Scanning electron microscope image of precursor A in Comparative Example 1;
[0051] Figure 17 EDS image of nickel disulfide composite hard carbon material in Comparative Example 2;
[0052] Figure 18 Scanning electron microscope image of precursor C in Comparative Example 3;
[0053] Figure 19 Scanning electron microscope image of precursor C in Comparative Example 4. DETAILED DESCRIPTION
[0054] To further explain the invention content, features and actual effects of the present application, the following detailed description of the present application is combined with examples. It should be noted that the design of the modification method of the present application is not limited to these specific embodiments. Without departing from the spirit and content of the present application, equivalent substitutions and modifications made by those skilled in the art on the basis of the content of the present application are also within the scope of the present application.
[0055] The following exemplary describes the preparation method of the high-capacity sodium ion battery negative electrode material provided by the present application.
[0056] The carbon material substrate is mixed with a transition metal salt solution, stirred and dried at 60-90℃ for 1-20 hours, then transferred to a crucible and placed in an inert atmosphere, heated to 400-1000℃ at a heating rate of 1-20℃ / min, high-temperature treated for 1-10h, and then naturally cooled to obtain a carbon material substrate with transition metal particles loaded on the surface.
[0057] In an optional embodiment, the solvent of the transition metal salt solution is at least one of water, ethanol, and acetone; the transition metal salt is an organic salt or an inorganic salt of the transition metal; the organic salt is at least one of formate, acetate, ethanolate, citrate, and acetylacetone; the inorganic salt is at least one of hydrochloride, sulfate, nitrate, phosphate, hypophosphite, chlorate, perchlorate, and sulfamate; the selection of different transition metal salts will affect the morphology of transition metal particles on the surface of the carbon substrate, thereby affecting the etched pore structure; the molar concentration of the transition metal salt solution is 0.01-2mol / L. The molar ratio of carbon elements in the carbon material substrate to transition metal elements in the transition metal sulfide is (50-1):1, preferably (40-3):1. If the molar ratio of carbon elements in the carbon material substrate to transition metal elements in the transition metal sulfide is not within the above range, too much transition metal will cause the fusion of particles to obtain the desired morphology, too large particles will be difficult to achieve etching effect in kinetics, and the generated transition metal sulfide will stay on the surface, resulting in poor cycle performance; too little transition metal will result in too low amount of generated transition metal sulfide, which cannot significantly increase the specific capacity of the material.
[0058] The inert atmosphere is at least one of argon, nitrogen, helium, and carbon monoxide; the flow rate of the inert atmosphere is 50-1000mL / min.
[0059] The particle size of the transition metal particles is 5nm-2μm.
[0060] The reason of loading transition metal particles on the surface of carbon material substrate in the application: as catalyst for etching to etch pore structure, as precursor for in-situ synthesis of transition metal sulfide.
[0061] The carbon material substrate with surface loaded transition metal particles is heated to etching temperature under inert atmosphere, and etchant is introduced, under the catalysis of transition metal, etchant etches along transition metal loading site, and transition metal particles enter inside along pore channel during etching process to form porous carbon material substrate with embedded transition metal particles.
[0062] In optional embodiment, the flow rate of inert atmosphere is 50-1000 mL / min.
[0063] The etching temperature is 700-1000℃, the time is 0.5-10h, and the heating rate is 1-20℃ / min.
[0064] With the increase of etching time, the etching depth of pore channel increases; the increase of etching temperature on one hand accelerates the fusion of transition metal particles, increases the particle size, and makes the etching pore diameter increase, and on the other hand accelerates the reaction activity, and makes the etching degree increase; too long etching time may make the material etched into "thousand holes", and too short etching time makes the transition metal particles still stay on the surface; too low etching temperature reduces the reaction activity, and makes the reaction unable to proceed.
[0065] The etchant is alkali etchant or gas etchant; the alkali etchant is sodium hydroxide, lithium hydroxide or potassium hydroxide; the gas etchant is water vapor or oxygen; the introduction mode of alkali etchant is that the alkali etchant and the carbon material substrate with loaded transition metal particles are pre-ground uniformly before heating. The molar ratio of alkali etchant to carbon material substrate with loaded transition metal particles is 1:10-10:1. The introduction mode of gas etchant is that the gas etchant with flow rate of 0.05-1 mL / min is introduced at etching temperature. When the etchant is alkali etchant, the method for removing alkali etchant is to use deionized water to dissolve and wash away alkali and reaction by-products.
[0066] The purpose of etching pore on carbon material substrate in the application is to provide a path for electrolyte to enter the inside of carbon material, to provide ion transmission channel, and to improve the rate performance; the etched pore structure makes transition metal sulfide generated inside the carbon material and constrained by pore wall.
[0067] The etching pore diameter in the application should be in a suitable range, and too large pore diameter makes transition metal sulfide particles too large, and the internal conductivity of particles decreases, and the sodium storage activity decreases.
[0068] The porous carbon material substrate embedded with transition metal particles is pre-mixed with sulfur powder, and high-temperature sulfuration is performed under an inert atmosphere to in-situ synthesize transition metal sulfide within the porous structure.
[0069] In an optional embodiment, the molar ratio of the sulfur powder to the carbon material substrate is (1-8):1; preferably, the molar ratio of the sulfur powder to the carbon material substrate is (2-4):1. If the molar ratio of the sulfur powder to the carbon material substrate is not within the above range, excessive sulfur powder is likely to remain in the carbon substrate, and sulfur produces polysulfides in the reaction, and the shuttle effect causes performance degradation; too small a molar ratio of the sulfur powder to the carbon material substrate causes incomplete reaction of the transition metal sulfide, lower valence of the transition metal, and lower sodium storage capacity.
[0070] The high-temperature sulfuration is a stepwise temperature rising process, including: rising the temperature to 95-300℃ at a temperature rising rate of 1-10℃ / min and maintaining for 1-10 hours, and continuously rising the temperature to 450-700℃ and maintaining for 1-12 hours.
[0071] The purpose of embedding the transition metal sulfide in the etched interior is to inhibit expansion of the transition metal sulfide by the pore structure and increase the electronic conductivity of the carbon substrate.
[0072] Carbon coating is performed on the surface of the high-capacity sodium ion negative electrode material.
[0073] In an optional embodiment, the carbon coating includes: using sucrose or pitch as a carbon source, dissolving in a solvent, mixing with the high-capacity sodium ion negative electrode material, and drying, pyrolyzing under an inert atmosphere to form a carbon coating structure on the surface of the high-capacity sodium ion negative electrode material; wherein the mass ratio of the carbon source to the high-capacity sodium ion negative electrode material is 3:20-1:1; the solvent is at least one of deionized water, ethanol, tetrahydrofuran, and isopropanol; the temperature for stirring and drying is 40-120℃, and the time is 0.5-12 hours; the temperature for pyrolysis is 400-1000℃, the time is 1-12 hours, and the temperature rising rate is 1-10℃ / min. The carbon coating can inhibit the shuttle effect of polysulfides in the reaction process.
[0074] The carbon coating can isolate the inside of the pores from the outside of the pores, limit the flow of electrolyte, inhibit the dissolution of polysulfides in the electrolyte and inhibit the passage of polysulfides through the separator, thereby inhibiting the shuttle effect in the reaction process.
[0075] The following further illustrates the embodiments in detail. It should also be understood that the following embodiments are only used to further illustrate the present application and cannot be understood as limiting the scope of the present application. Some non-essential improvements and adjustments made by those skilled in the art according to the above content of the present application are within the scope of the present application. The specific process parameters and the like described below are only one example in the appropriate range, that is, those skilled in the art can make appropriate selection within the range according to the description herein, and are not limited to the specific values of the following examples.
[0076] Example 1
[0077] (1) 1.244 g of nickel acetate tetrahydrate (0.005 mol) was dissolved in a mixture of 9 mL of water + 1 mL of alcohol to obtain solution A, and then 2.4 g of hard carbon (0.2 mol) was dispersed in solution A, and stirred and dried at 80°C for 2 h (the molar ratio of carbon atoms to nickel atoms was 40:1), and the precursor A was obtained after drying.
[0078] (2) The obtained precursor A was placed in a corundum crucible with a cover, and placed in a vacuum tube furnace, and argon was introduced at a flow rate of 100 mL / min, and the temperature rising program was set as follows: the temperature rising rate was 5°C / min, and the temperature was raised to 600°C for 2 h, and then naturally cooled after holding for 2 h, and the precursor B was obtained.
[0079] (3) The obtained precursor B was placed in a nickel crucible, and placed in a vacuum tube furnace, and argon was introduced at a flow rate of 60 mL / min, and water vapor was introduced at a flow rate of 0.1 mL / min, and the temperature rising program was set as follows: the temperature rising rate was 5°C / min, and the temperature was raised to 700°C for 140 min, and then naturally cooled after holding for 2 h, and the precursor C was obtained.
[0080] (4) The precursor C and 0.641 g of sulfur powder (0.02 mol) were mixed with a mortar, and placed in a corundum crucible, and placed in a vacuum tube furnace, and argon was introduced at a flow rate of 50 mL / min. The temperature rising program was set as follows: the temperature was raised to 150°C at a temperature rising rate of 10°C / min, and held for 4 h, and then the temperature was raised to 500°C at a temperature rising rate of 10°C / min, and the argon flow rate was adjusted to 200 mL / min, and held for 2 h, and naturally cooled to obtain a nickel disulfide composite hard carbon high specific capacity sodium ion negative electrode material.
[0081] Battery performance test: The sodium-ion battery negative electrode material, conductive carbon black and sodium carboxymethyl cellulose were mixed in a ratio of 7:2:1 with deionized water as the solvent to prepare a battery negative electrode slurry, which was coated on a 10 μm thick aluminum foil. After vacuum drying at 80°C for 10 h, it was cut into a 12 mm diameter disc. With a piece of metallic sodium as the counter electrode, a whatman glass fiber membrane as the separator, and a solution of NaClO4(1 mol / L) dissolved in propylene carbonate and ethylene carbonate (volume ratio 1:1) as the electrolyte, a CR2032 type battery was assembled in an argon glove box. After the battery was assembled, it was left to stand for 8 h, and then constant current charge and discharge tests were performed at a voltage of 2.5-0.01 V and a charge and discharge current density of 40 mA / g.
[0082] Figure 1 A scanning electron microscope image of the nickel particles supported on the surface of hard carbon after decomposition of the nickel acetate in Example 1, from which it can be seen that the nickel particles are uniformly supported on the surface of the carbon matrix.
[0083] Figure 2 A scanning electron microscope image of the nickel particles etched into the hard carbon after water vapor etching in Example 1, from which it can be seen that the nickel particles produce etching holes after etching and move into the carbon matrix.
[0084] Figure 3 A scanning electron microscope image of the nickel disulfide composite hard carbon material obtained after in-situ sulfidation in Example 1, from which it can be seen that the sulfided nickel disulfide particles are embedded in the carbon matrix.
[0085] Figure 4 A charge and discharge curve of the nickel disulfide composite hard carbon material in Example 1, the first cycle discharge specific capacity is: 427.46 mAh g -1 , the coulombic efficiency is: 84.32%; the second cycle discharge capacity is: 322.44 mAh g -1 .
[0086] Example 2
[0087] (1) 1.285 g of nickel acetylacetonate (0.005 mol) was dissolved in a mixture of 9 mL of water + 1 mL of alcohol to obtain solution A, then 2.4 g of hard carbon (0.2 mol) was dispersed in solution A, stirred and dried at 80°C for 2 h (molar ratio of carbon atoms to nickel atoms was 40:1), and after drying, precursor A was obtained.
[0088] (2) The obtained precursor A was placed in a corundum crucible with a cover, and placed in a vacuum tube furnace, and argon was introduced at a flow rate of 100 mL / min. The temperature rising program was set as follows: the temperature rising rate was 5°C / min, and the temperature was raised to 600°C for 2 h, and then naturally cooled after holding for 2 h, to obtain precursor B.
[0089] (3) Put the obtained precursor B into a nickel crucible, place it in a vacuum tube furnace, and introduce argon gas at a flow rate of 60 mL / min, while introducing water vapor at a flow rate of 0.1 mL / min. Set the temperature rising program as follows: the temperature rising rate is 5 ℃ / min, the temperature is raised to 700 ℃ in 140 min, and then the temperature is kept for 2 h before natural cooling, to obtain precursor C.
[0090] (4) Mix the precursor C with 0.641 g of sublimed sulfur powder (0.02 moL) in a mortar, and place it in a corundum crucible in a vacuum tube furnace, and introduce argon gas at a flow rate of 50 mL / min. Set the temperature rising program as follows: the temperature is raised to 150 ℃ at a temperature rising rate of 10 ℃ / min, and then kept for 4 h, and then the temperature is raised to 500 ℃ at a temperature rising rate of 10 ℃ / min, and then the argon gas flow rate is adjusted to 200 mL / min, and then kept for 2 h, and then naturally cooled to obtain a nickel disulfide composite hard carbon high specific capacity sodium ion negative electrode material.
[0091] Battery performance test: The sodium ion battery negative electrode material, conductive carbon black and sodium carboxymethyl cellulose are mixed in a ratio of 7:2:1 with deionized water as the solvent to prepare a battery negative electrode slurry, which is coated on a 10 μm thick aluminum foil, vacuum dried at 80 ℃ for 10 h, and then cut into a 12 mm diameter disc. With a metal sodium sheet as the counter electrode, a whatman glass fiber membrane as the separator, and a solution of NaClO4 (1 mol / L) dissolved in propylene carbonate and ethylene carbonate (volume ratio 1:1) as the electrolyte, a CR2032 type battery is assembled in an argon glove box. After the battery is assembled, it is left to stand for 8 h, and then constant current charge and discharge test is carried out, the test voltage is 2.5-0.01 V, and the charge and discharge current density is 40 mA / g.
[0092] Figure 5 The scanning electron microscope image of the nickel particles supported on the surface of the hard carbon after the decomposition of the acetylacetone nickel in Example 2, as shown in the figure, the nickel particles are relatively Figure 1 smaller in size.
[0093] Figure 6 The scanning electron microscope image of the nickel particles etched into the hard carbon after the water vapor etching in Example 2, as shown in the figure, the nickel particles are relatively smaller in size, and the etching holes are also smaller.
[0094] Figure 7 The scanning electron microscope image of the nickel disulfide composite hard carbon material obtained after in-situ sulfurization in Example 2, as shown in the figure, the nickel disulfide particles after sulfurization are expanded and embedded in the pores of the hard carbon.
[0095] Figure 8 The charge and discharge curve of the nickel disulfide composite hard carbon material in Example 3, the first circle discharge specific capacity is: 442.11 mAh g -1, the coulombic efficiency is: 83.34%; the second circle discharge capacity is: 339.42mAh g -1 .
[0096] Example 3
[0097] The surface of the high specific capacity sodium ion negative electrode material obtained in Example 1 is carbon-coated.
[0098] (1) Take sucrose 0.6g, dissolved in 5mL deionized water + 1mL alcohol mixed solution, take the negative electrode material 1.8g synthesized in Example 1, dispersed in the mixed solution, 80℃ stirring and drying 2h, get precursor D.
[0099] (2) Put the precursor D in the corundum crucible, put it in the vacuum tube furnace, pass in argon, the flow rate is 50mL / min, the temperature is raised to 400℃ at the rate of 5℃ / min, keep warm for 2h, then cool naturally, get carbon-coated nickel disulfide composite hard carbon material.
[0100] Battery performance test: the sodium ion battery negative electrode material, conductive carbon black and sodium carboxymethyl cellulose are mixed in a ratio of 7:2:1 with deionized water as the solvent to prepare a battery negative electrode slurry, which is coated on a 10μm thick aluminum foil, vacuum dried at 80℃ for 10h, and then cut into a 12mm diameter disc. With metal sodium sheet as the counter electrode, whatman glass fiber membrane as the separator, with propylene carbonate and ethylene carbonate solution containing NaClO4(1mol / L) as the electrolyte, in the argon protection glove box, assemble into CR2032 type battery. After the battery is assembled, it is placed for 8h, and then the constant current charge and discharge test is carried out, the test voltage is 2.5~0.01V, and the charge and discharge current density is 40mA / g.
[0101] Figure 9 It is the scanning electron microscope image of the carbon-coated nickel disulfide composite hard carbon material in Example 3, from the figure, the carbon layer can completely wrap the nickel disulfide inside the hard carbon.
[0102] Figure 10 It is the charge and discharge curve of the carbon-coated nickel disulfide composite hard carbon material in Example 3, the first circle discharge specific capacity is: 390.84mAh g -1 , the coulombic efficiency is: 83.52%; the second circle discharge capacity is: 309.02mAh g -1 .
[0103] Example 4
[0104] (1) 4.977 g of nickel acetate tetrahydrate (0.02 mol) was dissolved in a mixture of 9 mL of water and 1 mL of alcohol to obtain solution A, and then 1.2 g of expanded graphite (0.1 mol) was dispersed in solution A, and stirred and dried at 80°C for 2 h (molar ratio of carbon atoms to nickel atoms was 5:1) to obtain precursor A.
[0105] (2) The obtained precursor A was placed in a corundum crucible with a cover, and placed in a vacuum tube furnace, and argon was introduced at a flow rate of 100 mL / min. The temperature rising program was set as follows: the temperature rising rate was 5°C / min, and the temperature was raised to 600°C for 2 h, and then naturally cooled to obtain precursor B.
[0106] (3) The obtained precursor B was placed in a nickel crucible, and placed in a vacuum tube furnace, and argon was introduced at a flow rate of 60 mL / min, and water vapor was introduced at a flow rate of 0.1 mL / min. The temperature rising program was set as follows: the temperature rising rate was 5°C / min, and the temperature was raised to 700°C for 140 min, and then naturally cooled for 4 h to obtain precursor C.
[0107] (4) The precursor C was mixed with 2.565 g of sulfur sublimation powder (0.08 mol) in a mortar, and placed in a corundum crucible, and placed in a vacuum tube furnace, and argon was introduced at a flow rate of 50 mL / min. The temperature rising program was set as follows: the temperature was raised to 150°C at a temperature rising rate of 10°C / min, and then the temperature was raised to 500°C at a temperature rising rate of 10°C / min, and the argon flow rate was adjusted to 200 mL / min, and then the temperature was kept for 2 h, and then naturally cooled to obtain a nickel disulfide composite expanded graphite high specific capacity sodium ion negative electrode material.
[0108] Battery performance test: The sodium ion battery negative electrode material, conductive carbon black and sodium carboxymethyl cellulose were mixed in a ratio of 7:2:1 with deionized water as the solvent to prepare a battery negative electrode slurry, which was coated on a 10 μm thick aluminum foil, vacuum dried at 80°C for 10 h, and then cut into a 12 mm diameter disc. A metal sodium sheet was used as the counter electrode, a whatman glass fiber membrane was used as the separator, and a solution of NaClO4 (1 mol / L) dissolved in propylene carbonate and ethylene carbonate (volume ratio 1:1) was used as the electrolyte to assemble a CR2032 type battery in an argon protective glove box. After the battery was assembled, it was left to stand for 8 h, and then constant current charge and discharge test was performed, the test voltage was 3-0.01 V, and the charge and discharge current density was 40 mA / g. The cyclic voltammetry test used a battery that was left to stand for 8 h after assembly, the scan rate was 0.1 mV / s, the voltage range was 3-0.01 V, and the cycle was 2 times.
[0109] Figure 11 The scanning electron microscope image of the nickel disulfide composite expanded graphite material obtained by in-situ sulfurization in Example 4 is shown in the figure, and it can be seen that most of the nickel disulfide can be embedded in the expanded graphite.
[0110] Figure 12 For the X-ray diffraction pattern of the nickel disulfide composite expanded graphite material in Example 4, it can be seen that the phases are graphite and nickel disulfide, and from the figure it can be seen that the synthesized nickel disulfide has a relatively pure phase.
[0111] Figure 13 For the charge-discharge curve of the nickel disulfide composite expanded graphite material in Example 4, from the figure it can be seen that the first circle discharge capacity is: 700.43 mAh g -1 , the coulombic efficiency is: 98.12%; the second circle discharge capacity is: 580.83 mAh g -1 .
[0112] Figure 14 For the cyclic voltammetry curve of the nickel disulfide composite expanded graphite material in Example 4, from the figure it can be seen that the cathode peak of 0.93V in the first circle is the intercalation reaction of sodium ions in NiS2, from the second circle, the cathode peaks of 1.45V and 0.91V respectively represent the process of NiS2 converting into intermediate Na x NiS2and the intermediate converting into Ni and NaS2, the anode peaks of 1.66V and 1.97V respectively represent the process of Ni and NaS2 converting into intermediate Na x NiS2and the intermediate converting into NiS2.
[0113] Example 5
[0114] (1) 1.244 g of nickel acetate tetrahydrate (0.005 moL) was dissolved in a mixture of 9 mL of water + 1 mL of alcohol to obtain solution A, then 1.2 g of hard carbon (0.1 moL) was dispersed in solution A, and stirred and dried at 80℃ for 2h (the molar ratio of carbon atoms to nickel atoms was 20:1), and after drying, precursor A was obtained.
[0115] (2) The obtained precursor A was placed in a corundum crucible with a cover, placed in a vacuum tube furnace, argon was introduced at a flow rate of 100 mL / min, and the temperature rising program was set as follows: the temperature rising rate was 5℃ / min, and the temperature was raised to 600℃ for 2h, and then naturally cooled after holding for 2h, to obtain precursor B.
[0116] (3) The obtained precursor B was placed in a nickel crucible, placed in a vacuum tube furnace, argon was introduced at a flow rate of 60 mL / min, and water vapor was introduced at the same time, the water amount was 0.1 mL / min, the temperature rising program was set as follows: the temperature rising rate was 5℃ / min, and the temperature was raised to 700℃ for 140 min, and then naturally cooled after holding for 2h, to obtain precursor C.
[0117] (4) The precursor C is mixed with 0.641 g of sublimed sulfur powder (0.02 mol) in a mortar, placed in a corundum crucible, and placed in a vacuum tube furnace, and argon gas is introduced at a flow rate of 50 mL / min. The temperature rising program is set as follows: the temperature is raised to 150°C at a rate of 10°C / min, and after 4 h of heat preservation, the temperature is raised to 500°C at a rate of 10°C / min, the argon gas flow rate is adjusted to 200 mL / min, and after 2 h of heat preservation, the natural cooling is performed to obtain a nickel disulfide composite hard carbon high specific capacity sodium ion negative electrode material.
[0118] Battery performance test: The sodium ion battery negative electrode material, conductive carbon black and sodium carboxymethyl cellulose are mixed in a ratio of 7:2:1 with deionized water as the solvent to prepare a battery negative electrode slurry, which is coated on a 10 μm thick aluminum foil, vacuum dried at 80°C for 10 h, and then cut into a 12 mm diameter disc. A metal sodium sheet is used as the counter electrode, a whatman glass fiber membrane is used as the separator, and a solution of NaClO4 (1 mol / L) dissolved in propylene carbonate and ethylene carbonate (volume ratio 1:1) is used as the electrolyte to assemble a CR2032 type battery in an argon gas protected glove box. After the battery is assembled, it is left to stand for 8 h, and then constant current charge and discharge test is performed, the test voltage is 2-0.01 V, and the charge and discharge current density is 40 mA / g.
[0119] Figure 15 The charge and discharge curves of the nickel disulfide composite hard carbon material in Example 5 are as follows: the first cycle discharge specific capacity is 442.11 mAh g -1 , and the coulombic efficiency is 83.34%; the second cycle discharge capacity is 339.42 mAh g -1 .
[0120] Comparative Example 1
[0121] The preparation process of the nickel disulfide composite hard carbon high specific capacity sodium ion negative electrode material in this comparative example 1 refers to Example 5, and the only difference is that in step (1), 49.76 g of nickel acetate tetrahydrate (0.2 mol) is dissolved in a mixture of 9 mL of water + 1 mL of alcohol to obtain solution A, and then 1.2 g of hard carbon (0.1 mol) is dispersed in solution A, and stirred and dried at 80°C for 2 h (the molar ratio of carbon atoms to nickel atoms is 1:2), and after drying, the precursor A is obtained.
[0122] Figure 16 The scanning electron microscope image of the precursor A in Comparative Example 1 shows that a large amount of nickel is wrapped around the surface of the hard carbon, and cannot play the role of point etching.
[0123] Comparative Example 2
[0124] The preparation process of the nickel disulfide composite hard carbon high specific capacity sodium ion negative electrode material in Comparative Example 2 refers to Example 5, and the only difference is that in step (4), the precursor C is mixed with 0.160 g of sulfur powder (0.005 moL) in a mortar, placed in a corundum crucible, and placed in a vacuum tube furnace, and argon is introduced at a flow rate of 50 mL / min. The temperature rising program is set as follows: the temperature is raised to 150°C at a rate of 10°C / min, and after 4 h of heat preservation, the temperature is raised to 500°C at a rate of 10°C / min, the argon flow rate is adjusted to 200 mL / min, and after 2 h of heat preservation, the natural cooling is obtained to obtain the nickel disulfide composite hard carbon high specific capacity sodium ion negative electrode material.
[0125] Figure 17 The EDS image of the nickel disulfide composite hard carbon material in Comparative Example 2 is shown in the figure, and it can be seen that the nickel is not fully sulfided to nickel disulfide.
[0126] Comparative Example 3
[0127] The preparation process of the nickel disulfide composite hard carbon high specific capacity sodium ion negative electrode material in Comparative Example 3 refers to Example 5, and the only difference is that in step (3), the obtained precursor B is placed in a nickel crucible and placed in a vacuum tube furnace, and argon is introduced at a flow rate of 60 mL / min, and water vapor is introduced at the same time, with a water amount of 0.1 mL / min, and the temperature rising program is set as follows: the temperature is raised to 700°C at a rate of 5°C / min for 140 min, and after 0.2 h of heat preservation, the natural cooling is obtained to obtain the precursor C.
[0128] Figure 18 The scanning electron microscope image of the precursor C in Comparative Example 3 is shown in the figure, and it can be seen that the etching degree is insufficient, and the nickel does not enter the inside of the hard carbon.
[0129] Comparative Example 4
[0130] The preparation process of the nickel disulfide composite hard carbon high specific capacity sodium ion negative electrode material in Comparative Example 4 refers to Example 5, and the only difference is that in step (3), the obtained precursor B is placed in a nickel crucible and placed in a vacuum tube furnace, and argon is introduced at a flow rate of 60 mL / min, and water vapor is introduced at the same time, with a water amount of 0.1 mL / min, and the temperature rising program is set as follows: the temperature is raised to 650°C at a rate of 5°C / min for 140 min, and after 2 h of heat preservation, the natural cooling is obtained to obtain the precursor C.
[0131] Figure 19 The scanning electron microscope image of the precursor C in Comparative Example 4 is shown in the figure, and it can be seen that the temperature is insufficient, and the nickel and the hard carbon cannot occur etching reaction.
Claims
1. A high-capacity sodium ion battery negative electrode material, characterized in that The high-capacity sodium ion battery negative electrode material includes a carbon material substrate and a transition metal sulfide grown in situ and embedded in the carbon material substrate; wherein the molar ratio of the carbon element in the carbon material substrate to the transition metal element in the transition metal sulfide is (50-1):
1. The preparation method of the high-capacity sodium ion battery negative electrode material includes: (1) mixing a carbon material substrate with a transition metal salt solution, stirring and drying to obtain a carbon material substrate with a surface loaded with a transition metal salt, and subjecting the mixture to high temperature treatment under an inert atmosphere to obtain a carbon material substrate with a surface loaded with transition metal particles; (2) introducing an etchant into the obtained carbon material substrate loaded with transition metal particles under an inert atmosphere and etching it under heating conditions to form a porous structure in the carbon material substrate and embed the transition metal particles into the porous structure to form a porous carbon material substrate embedded with transition metal particles; (3) Premixing a porous carbon material substrate embedded with transition metal particles with sulfur powder and performing high-temperature sulfurization under an inert atmosphere to in situ synthesize transition metal sulfides within the porous structure.
2. The high-capacity sodium ion battery negative electrode material according to claim 1, characterized in that The molar ratio of the carbon element in the carbon material substrate to the transition metal element in the transition metal sulfide is (40-3):
1.
3. The high-capacity sodium ion battery negative electrode material according to claim 1, characterized in that The transition metal in the transition metal sulfide is at least one of Mo, Co, Fe, Ni, and Mn; The carbon material substrate is hard carbon, soft carbon, graphite, expanded graphite, mesophase carbon microspheres or carbon fibers.
4. The high-capacity sodium ion battery negative electrode material according to claim 1, wherein In step (1), the solvent of the transition metal salt solution is at least one of water, ethanol, and acetone; the transition metal salt is an organic salt or an inorganic salt of a transition metal; the organic salt is at least one of formate, acetate, ethanol, citrate, and acetylacetonate; the inorganic salt is at least one of hydrochloride, sulfate, nitrate, phosphate, hypophosphite, chlorate, perchlorate, and sulfamate; and the molar concentration of the transition metal salt solution is 0.01 to 2 mol / L.
5. The high-capacity sodium ion battery negative electrode material according to claim 1, characterized in that In step (1), the stirring and drying temperature is 60 to 90° C. and the time is 1 to 20 hours; The inert atmosphere is at least one of argon, nitrogen, helium, and carbon monoxide; the flow rate of the inert atmosphere is 50 to 1000 mL / min; The temperature of the high temperature treatment is 400-1000° C., the time is 1-10 hours, and the heating rate is 1-20° C. / min.
6. The high-capacity sodium ion battery negative electrode material according to claim 5, characterized in that In step (1), the temperature of the high temperature treatment is 500-700°C, the time is 1-4 hours, and the heating rate is 5-10°C / min.
7. The high-capacity sodium ion battery negative electrode material according to claim 1, characterized in that In step (1), the particle size of the transition metal particles is 5 nm to 2 μm.
8. The high-capacity sodium ion battery negative electrode material according to claim 1, characterized in that In step (2), the etching specifically includes: heating the carbon material substrate with transition metal particles loaded on the surface to the etching temperature under an inert atmosphere, introducing an etchant, and under the catalytic action of the transition metal particles, the etchant etches along the loading sites of the transition metal particles, and the transition metal particles enter the interior along the pores during the etching process.
9. The high-capacity sodium ion battery negative electrode material according to claim 8, characterized in that In step (2), the flow rate of the inert atmosphere is 50 to 1000 mL / min; The etching temperature is 700-1000°C, the time is 0.5-10 hours, and the heating rate is 1-20°C / min; The etchant is an alkaline etchant or a gas etchant; the alkaline etchant is sodium hydroxide, lithium hydroxide or potassium hydroxide; the gas etchant is water vapor or oxygen; the alkaline etchant is introduced by pre-grinding the alkaline etchant and the carbon material substrate loaded with transition metal particles uniformly before heating; the molar ratio of the alkaline etchant to the carbon material substrate loaded with transition metal particles is 1:10 to 10:1; The gas etchant is introduced in the following manner: at an etching temperature, the gas etchant is introduced at a flow rate of 0.05 to 1 mL / min; When the etchant is an alkali etchant, the method for removing the alkali etchant is: using deionized water to dissolve and wash away the alkali and its reaction by-products.
10. The high-capacity sodium ion battery negative electrode material according to claim 1, characterized in that In step (3), the molar ratio of the sulfur powder to the carbon material substrate is (1-8):1; The high temperature vulcanization is a step-by-step temperature increase procedure, including: heating to 95°C to 300°C at a heating rate of 1 to 10°C / min and keeping the temperature for 1 to 10 hours, and then continuing to heat to 450°C to 700°C and keeping the temperature for 1 to 12 hours.
11. The high-capacity sodium ion battery negative electrode material according to claim 10, characterized in that In step (3), the molar ratio of the sulfur powder to the carbon material substrate is (2-4):
1.
12. The high-capacity sodium ion battery negative electrode material according to claim 1, characterized in that The preparation method also includes: performing carbon coating on the surface of the high-capacity sodium ion battery negative electrode material; the carbon coating includes: using sucrose or asphalt as a carbon source, dissolving it in a solvent, mixing it with the high-capacity sodium ion negative electrode material, stirring and drying it, and pyrolyzing it under an inert atmosphere to form a carbon coating structure on the surface of the high-capacity sodium ion negative electrode material; wherein the mass ratio of the carbon source to the high-capacity sodium ion negative electrode material is 3:20 to 1:1; the solvent is at least one of deionized water, ethanol, tetrahydrofuran, and isopropanol; the temperature of the stirring and drying is 40 to 120°C, and the time is 0.5 to 12 hours; the temperature of the pyrolysis is 400 to 1000°C, and the time is 1 to 12 hours, and the heating rate is 1 to 10°C / min.
Citation Information
Patent Citations
Preparation methods of transition metal carbide, carbon material and transition metal chalcogenide and application of transition metal chalcogenide
CN110921668A
Iron sulfide@sulfur hybrid porous carbon positive electrode precursor material and preparation and application of sulfur-loaded positive electrode active material thereof
CN111217355A